Genesis of the Segments ‘Vocabularium’ and ‘Mythologie Universelle’ in Simonas Daukantas’s Manuscript Margumynai - Subačius, Giedrius (Senoji Lietuvos literatūra, 2019)
Parts of Simonas Daukantas’s manuscript Margumynai, preserved in the library of the Institute of Lithuanian Literature and Folklore in Vilnius (f. 1 – SD 27), constitute segments that Daukantas titled ‘Vocabularium’ (Voc) and ‘Mythologie universelle’ (MU). They are mostly lists of Greek, French, and Lithuanian words. The sources of both Voc and MU were identified. In Voc, Daukantas reused the Greek words and their French translations from the French dictionary by Pierre Claude Victoire Boiste Dictionnaire Universel de la langue Française (1834, the eight corrected and enlarged edition). Analogously, the Greek words and their French explanations in MU were taken from one appendix at the end of Boiste’s same dictionary: Vocabulaire de Mythologie Universelle, Ancienne et Moderne de tous les Peuples, Avec les Étymologies Grecque, Latine, etc. Daukantas placed Lithuanian words next to the Greek ones. He selected Lithuanian lexemes for their certain resemblance to the form of the Greek counterparts, but the meaning of the juxtaposed lexical items remained distant at best. Daukantas only associated Lithuanian words with the Greek ones; he did not try to translate them. Certain orthographic features of Voc and MU (and also of some other smaller Lithuanian texts inscribed between the two) are similar to Daukantas’s earlier manuscripts of 1834–1835 (<-ay, -ey>, <ů>, ), and some other peculiarities (<-îs>; stable <-ys>; double ) coincide with those of Daukantas’s later book Prasma Łotynû kałbos (A Grammar of Latin) of 1837. Thus, Voc and MU were compiled by Daukantas during the span between those earlier manuscripts of 1834–1835 and Prasma of 1837. In addition, sources of some other texts that Daukantas copied into his Margumynai manuscript enable us to date Daukantas’s manuscripts even more precisely: Voc must have been compiled in 1835, and MU—sometime between 9 July and 20 August 1836.